UPAYA GURU PKn DALAM MEMBANGUN KARAKTER DISIPLIN DAN NILAI – NILAI PANCASILA PADA SISWA KELAS VIII C SMP NEGERI 1 TELLU SIATTINGE - Selviani; Ilham; ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the efforts of Civic Education (PKn) teachers in building disciplinary character and Pancasila values among students of Class VIII C at SMP Negeri 1 Tellu Siattinge, Bone Regency. This research employed a qualitative research method. The data analyzed were obtained from interviews with the Civic Education teacher and students of Class VIII C at SMP Negeri 1 Tellu Siattinge. The data collection methods used in this study included observation, interviews, and document analysis, in which the researcher directly observed the actual conditions in the field. The results of the study indicate that the efforts of Civic Education teachers include providing role modeling, implementing classroom rules, giving positive reinforcement, applying educational sanctions, and integrating disciplinary values into teaching materials. Civic Education teachers play an active role in shaping students’ disciplinary attitudes through the learning process and habituation in daily school life.